Proses Komunikasi antara Sutradara dan Tim Produksi Film Dokumenter Mewujudkan Bandung: Lautan Literasi - Dewi Tri Wahyunningsih; Fajrin Al Maris; Dian Wardiana Sjuchro; Efi Fadilah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
Communication in documentary film production plays a crucial role in aligning creative visions, fostering coordination, and maintaining the team’s effectiveness at every stage of production. This study aims to describe the communication process between the director and the production team during the creation of the documentary Mewujudkan Bandung: Lautan Literasi in the pre-production, production, and post-production phases. The approach used is descriptive qualitative research employing a practice-based research method, which treats the creative process as the primary source of data collection and analysis. Data were collected through observation, interviews, literature review, and documentation during the production process. The findings of the discussion indicate that communication during the pre-production phase serves to establish a shared understanding of the story concept, develop a storyboard, assign tasks, and coordinate the production schedule. During the production phase, communication takes place directly and adaptively through direction given to the crew and interviewees, coordination of filming, and adjustments to various on-site challenges without compromising the director’s objectives. During the post-production phase, communication between the director and the editor focuses on developing the narrative structure, editing the footage, evaluating the results, and refining the message to ensure it remains consistent with the original concept. The entire communication process serves a function that is not limited to technical coordination but also acts as a collaborative mechanism for building a shared understanding and supporting decision-making,  as well as maintaining the quality and consistency of the presentation of literacy issues in the form of audiovisual works.